The Effect of Teamwork, Communication, and Work Discipline on Job Satisfaction at PT. Indonesia Synthetic Textile Mills - Hendra Suwardi; Pujiarti Pujiarti (Primanomics : Jurnal Ekonomi & Bisnis, 2026)
This study was conducted to find out and analyze the Influence of Teamwork, Communication, and Work Discipline on Employee Job Satisfaction at PT ISTEM. In conducting this study, the author used the saturated sampling method. There were 52 respondents who filled out the questionnaire (g-form) and were supported by SPSS version 25. From the results of the research that has been carried out, it is shown that the value of the Adjusted R Square is 0.710 or 71.0%, while for the rest, which is 29%, is explained by variables or other factors that are not explained in this regression analysis. Based on the t-test, it was shown that the variable X1 (Teamwork) had a value of 1.750 > 1.67655 with a significant value of 0.086 > 0.05, meaning that Ho was rejected Ha was accepted, the variable X2 (Communication) was 1.855 >1.67655 with a significant value of 0.070 > 0.05, meaning that Ho was rejected and Ha was accepted, the variable X3 (Work Discipline) was 2.987 > 1.67655 with a significant value of 0.004 < 0.05,  meaning that Ho is rejected and Ha is accepted. Based on the F test of 42.697 > 2.57 with a significant level of 0.000 < 0.05, it can be concluded that what means that Ho is rejected and Ha is accepted means that there is a simultaneous influence of independent variables on dependent variables.